Flexible Textile Strain Wireless Sensor Functionalized with Hybrid Carbon Nanomaterials Supported ZnO Nanowires with Controlled Aspect Ratio. (1st July 2016) - Lee, Taemin; Lee, Wonoh; Kim, Sung‐Woo; Kim, Jae Joon; Kim, Byeong‐Su
Abstract : Smart fabrics and interactive textiles have attracted great interest as a newly emergent material because of their multifunctional capabilities. Herein, a highly robust wireless flexible strain sensor on the basis of commercial textile by the integration of functional hybrid carbon nanomaterials and piezoresistive material is fabricated. Specifically, a solution‐processable spray‐assisted coating approach that enables the creation of a uniform coating over a large area of fabrics is employed. The textile‐based strain sensor exhibits a highly stable and immediate response over a wide range of bending curvatures and structural properties of ZnO nanowires because of their different deflection behaviors. The wearing performance with attaching on commercial fabrics is further demonstrated. The as‐prepared sensor responds well to diverse body motions with accurate detection of strain magnitude and even extends its viability in wireless remote sensing by connecting to a wireless transmitter. The novel approach for the modification of textiles with functional nanomaterials may provide a feasible approach for the production of textile‐based electronics without employing any sophisticated fabrication processes, and it further exploits the diverse functionalities by utilizing various sensing components. Abstract : A highly robust flexible strain sensor is fabricated through a facile integration of functional nanomaterials into a textile platform. It well demonstrates not only a rapid response to diverse body motions but also different strain sensing behaviors depending on geometrical features of ZnO nanostructure. Furthermore, the capability of the textile‐based sensor is extended to remote monitoring by configuration with wireless transmitter.